Suture exostosis with concurrent nasal septum chondrosarcoma in a horse. (13th February 2015) - Bonilla, A. G.; Wilson, K.; Santschi, E. M.
Summary A 15‐year‐old Hanoverian mare presented with a 10‐day history of facial swelling in the right maxillary and frontal regions, left epiphora and intermittent right epistaxis. Radiographs revealed suture exostosis of both nasofrontal sutures and a deviated and thickened nasal septum. Computed tomography (CT) of the skull revealed exostosis of the nasolacrimal sutures and ducts bilaterally of both nasofrontal sutures and of the right zygomatocomaxillary and lacrimomaxillary sutures. The mid‐to‐caudal aspect of the nasal septum was thickened and had multiple well demarcated hypoattenuated regions within the septum. Histological examination of biopsies taken from the right nasofrontal suture and the nasal septal mass revealed suture exostosis and nasal septum chondrosarcoma. The horse was treated with rest and anti‐inflammatories. The facial swelling and left epiphora were improved at 7 months telephone follow‐up. This report is the first to describe a nasal septum chondrosarcoma in a horse. Additionally, we suggest that the suture exostosis may have developed due to an alteration of the biomechanics of the skull sutures secondary to the septal tumour.